The Cytochrome P450 gene CYP6P12 confers pyrethroid resistance in kdr-free Malaysian populations of the dengue vector Aedes albopictus - Ishak, Intan H. (Sci Rep, 2016)
Control of Aedes albopictus, major dengue and chikungunya vector, is threatened by growing cases of insecticide resistance. The mechanisms driving this resistance remain poorly characterised. This study investigated the molecular basis of insecticide resistance in Malaysian populations of Ae. albopictus. Microarray-based transcription profiling revealed that metabolic resistance (cytochrome P450 up-regulation) and possibly a reduced penetration mechanism (consistent over-expression of cuticular protein genes) were associated with pyrethroid resistance. CYP6P12 over-expression was strongly associated with pyrethroid resistance whereas CYP6N3 was rather consistently over-expressed across carbamate and DDT resistant populations. Other detoxification genes also up-regulated in permethrin resistant mosquitoes included a glucuronosyltransferase (AAEL014279-RA) and the glutathione-S transferases GSTS1 and GSTT3. Functional analyses further supported that CYP6P12 contributes to pyrethroid resistance in Ae. albopictus as transgenic expression of CYP6P12 in Drosophila was sufficient to confer pyrethroid resistance in these flies. Furthermore, molecular docking simulations predicted CYP6P12 possessing enzymatic activity towards pyrethroids. Patterns of polymorphism suggested early sign of selection acting on CYP6P12 but not on CYP6N3. The major role played by P450 in the absence of kdr mutations suggests that addition of the synergist PBO to pyrethroids could improve the efficacy of this insecticide class and overcome resistance in field populations of Ae. albopictus.